Perception Public’s Regarding the Consumption of Coconut Water Before and After Covid-19 Vaccine in the Samaturue Village - Amalia; Muhammad Asikin; Umar, Fitriani (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: Vaccination efforts are carried out to reduce the transmission of covid-19, but the fear of the emergence of Adverse Events Following Immunization (AEFI) makes people worried and looking for anicipatory actions, namely by consumption of coconut water before and after covid-19 vaccine. Objectives: To find out public’s perception regarding the consmption of coconut water before and after covid-19 vaccine in Samaturue Village. Research Metodes: This study is a descriptive study with a sample of part of the community of Samaturue Village. Sampling with the purposive sampling method was 95 people.. Results: The reseach shows that as many as 72,6% people know that coconut water content can reduce fever. As many as 65,3% people agree to consume coconut water before and after the vaccine. People who consumed coconut water before the vaccine were 23,2%. Conclusion: From the results of research that has been carried out, the community knows the benefits and content of coconut water to relieve fever as much as 73,7%, the persection of consuming coconut water before and after covid-19 is 65,3%, then 23,2% of people who consume coconut water, the encouraging factor for consuming coconut water comes from themselvers with a percentage of 15,8%.